Linking Psychological Empowerment, Knowledge Sharing, and Employees’ Innovative Behavior in SMEs - Helmy, Irfan; Adawiyah, Wiwiek Rabiatul; Banani, Ade (The Journal of Behavioral Science, 2019)
The research aims to empirically verify the role of psychological empowerment in its contribution to innovative work behavior, with knowledge sharing as a mediating variable. This research was conducted in small and medium enterprises (SMEs) located in Yogyakarta, Indonesia, which is one of the provinces with the most significant growth of creative industries and tourism in Indonesia. The study used a quantitative approach with purposive sampling technique. Questionnaires were distributed to 500 employees from 50 SMEs from different types of businesses. Statistical analysis was conducted by using structural equation modeling with Smart-Partial Least Squares (PLS). The results show that the three dimensions of psychological empowerment: meaning (β=.09, p<.05), competence (β=.05, p<.01), and self-determination (β=.10, p<.01), were positively related to innovative work behavior. Furthermore, our findings showed that knowledge sharing partially mediated the relationship between meaning (β=.13, p<.05) and self-determination (β=.15, p<.05) to innovative work behavior, while full mediation for the impact dimension (β=.07, p<.01). These findings offer implications regarding how psychological empowerment can enhance innovative work behavior through knowledge sharing in SMEs.